2016
DOI: 10.1242/jeb.124024
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of lost endings: caudal autotomy as a lens for focusing attention on tail function during locomotion

Abstract: Autotomy has evolved in many animal lineages as a means of predator escape, and involves the voluntary shedding of body parts. In vertebrates, caudal autotomy (or tail shedding) is the most common form, and it is particularly widespread in lizards. Here, we develop a framework for thinking about how tail loss can have fitness consequences, particularly through its impacts on locomotion. Caudal autotomy is fundamentally an alteration of morphology that affects an animal's mass and mass distribution. These morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Considering first the deflective use of autotomic tails in lizards, despite the obvious defensive benefit, the resulting escape unavoidably comes at a cost. In many lizards, the tail acts as a fat store and so the loss of this fat store may make an individual more at risk from starvation (McConnachie & Whiting 2003;Gillis & Higham 2016). However, the distribution of energy reserves in species showing autotomy may mean that caudal fat storage does not always come into conflict with tail loss (Chapple & Swain 2002).…”
Section: Which Taxa Deflect Their Predators' Attacks and By What Mechmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering first the deflective use of autotomic tails in lizards, despite the obvious defensive benefit, the resulting escape unavoidably comes at a cost. In many lizards, the tail acts as a fat store and so the loss of this fat store may make an individual more at risk from starvation (McConnachie & Whiting 2003;Gillis & Higham 2016). However, the distribution of energy reserves in species showing autotomy may mean that caudal fat storage does not always come into conflict with tail loss (Chapple & Swain 2002).…”
Section: Which Taxa Deflect Their Predators' Attacks and By What Mechmentioning
confidence: 99%
“…However, the distribution of energy reserves in species showing autotomy may mean that caudal fat storage does not always come into conflict with tail loss (Chapple & Swain 2002). A lizard's tail also has other functions, such as balance (Ballinger 1973;Gillis et al 2009;Libby et al 2012;Gillis & Higham 2016) and thermoregulation (Martin & Salvador 1993), and so tail loss comes with a number of costs alongside loss of fat store and a predator avoidance mechanism. Fundamentally, caudal autotomy may alter an animal's morphology such that its mass and mass distribution are affected, influencing locomotor activities often critical for survival and reproduction (see Bateman & Fleming (2009) and Gillis & Higham 2016 and references therein).…”
Section: Which Taxa Deflect Their Predators' Attacks and By What Mechmentioning
confidence: 99%
“…While it has never been thoroughly investigated and little is known about their swimming habits, it has been suggested that mesosaurs could have used a sub-anguilliform (axial undulations that involve most of the body length, but especially the tail) mode of swimming 30,33 . If mesosaurs could autotomize their tails, this would have significantly affected their swimming capabilities and ability to catch prey 34 . The presence of autotomous caudal vertebrae in mesosaurs therefore leads us to question how important the tail was in propelling them through the water.…”
Section: Discussionmentioning
confidence: 99%
“…The tail is held off the ground as the lizard walks at a normal pace, the standing wave produced by locomotory undulations of the trunk being transmitted as a travelling wave producing undulations in the tail (Jagnandan & Higham, 2017). The tail is autotomic (Cheek, 2005;Jagnandan et al 2014;Lynn et al, 2013;Russell et al, 2015), and loss of the entire tail results in the instantaneous loss of a considerable amount of weight (20-23% of total body mass in juveniles [Lynn et al, 2013]; 25% of total body mass in adults [Jagnandan et al, 2014]), and to the sudden absence of an appendage that plays a significant locomotory role (Gillis & Higham, 2016;Jagnandan & Higham, 2017). E. macularius adopts a more sprawling locomotory posture after tail loss, principally through adjustment of the angles adopted by the segments of the hindlimb, and pelvic rotation is reduced (Jagnandan & Higham, 2017;Jagnandan et al, 2014), but walking speed is unaffected (Jagnandan & Higham, 2017).…”
Section: Discussionmentioning
confidence: 99%